Analyzing Students' Cognitive Process of Mathematical Problem Solving for Mathematical Literacy - Setiyani Setiyani; Nurul Ikhsan Karimah; Trusti Hapsari; Sri Sumarwati; Turini Erawati; Try Suprayo (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2024)
Math education aims to develop thinking skills and promote problem-solving using math. Unfortunately, students often find it dull, leading them to rely on memorization instead of grasping concepts. Mathematical literacy involves using math in everyday situations, requiring reasoning and concept application. This study used a descriptive qualitative method to explore how eighth-grade students approach math literacy problems from a cognitive perspective. The instruments used in this research include tests, interviews, observations, and documentation. Subjects were chosen by giving numeracy problems to 25 AKM program participants, and then three subjects were selected for in-depth interviews based on cognitive level. Data analysis involved data reduction, examining results and semi-structured interview responses for verbal expressions of thinking processes related to math literacy at different cognitive levels. Based on the results of this research, subjects with high abilities demonstrated a deep understanding of the problems, organized information very well, used prior knowledge and experience to make attempts, and engaged in reflection and evaluation of the answers obtained. In summary, students with varying cognitive levels showed good math literacy skills, as evidenced by all three subjects successfully meeting the descriptors of the thinking process when solving math literacy problems